Regulation of biotechnology in the European Community. - SZCZEPANIK, Valerie (1993)
Highlights the conflicting interests of the industrial, public and scientific sectors that the EC has had to balance in its regulatory equation, and details the effect the Directives have had on these sectors. Analyses the regulatory means chosen by the EC to implement its strategy for a common market and to provide for environmental protection.